Induced alkalosis and caffeine supplementation: Effects on 2,000-m rowing performance - Carr, A. J.; Gore, C. J.; Dawson, B. (International Journal of Sport Nutrition and Exercise Metabolism, 2011)
The purpose of this investigation was to determine the effect of ingested caffeine, sodium bicarbonate, and their combination on 2,000-m rowing performance, as well as on induced alkalosis (blood and urine pH and blood bicarbonate concentration [HCO3-]), blood lactate concentration ([La-]), gastrointestinal symptoms, and rating of perceived exertion (RPE). Methods: In a double-blind, crossover study, 8 well-trained rowers performed 2 baseline tests and 4 × 2,000-m rowing-ergometer tests after ingesting 6 mg/kg caffeine, 0.3 g/kg body mass (BM) sodium bicarbonate, both supplements combined, or a placebo. Capillary blood samples were collected at preingestion, pretest, and posttest time points. Pairwise comparisons were made between protocols, and differences were interpreted in relation to the likelihood of exceeding the smallest-worthwhile-change thresholds for each variable. A likelihood of >75% was considered a substantial change. Results: Caffeine supplementation elicited a substantial improvement in 2,000-m mean power, with mean (± SD) values of 354 ± 67 W vs. placebo with 346 ± 61 W. Pretest [HCO3-] reached 29.2 ± 2.9 mmol/L with caffeine + bicarbonate and 29.1 ± 1.9 mmol/L with bicarbonate. There were substantial increases in pretest [HCO3 -] and pH and posttest urine pH after bicarbonate and caffeine + bicarbonate supplementation compared with placebo, but unclear performance effects. Conclusions: Rowers` performance in 2,000-m efforts can improve by ~2% with 6 mg/kg BM caffeine supplementation. When caffeine is combined with sodium bicarbonate, gastrointestinal symptoms may prevent performance enhancement, so further investigation of ingestion protocols that minimize side effects is required.